PELATIHAN INOVASI PRODUK DAN PENGEMBANGAN BISNIS UMKM UNTUK MENAMBAH NILAI JUAL DAN DAYA SAING PASAR LOKAL: Product Innovation And MSME Business Development To Increase Selling Value And Local Market Competitiveness - Aminullah, Aminullah; Hamid, Hamid; Sativa, Denianto Yoga; Marini, Ida Ayu Ketut; Apriani, Titin; Sari, Ni Luh Ariningsih; Listyaningrum, Novita; Sari, Arlina Maya; Agustiawan, Dedi (Al-Amal: Jurnal Pengabdian Masyarakat, 2025)
This Community Service (PKM) program aims to provide training to the community for product innovation and MSME business development to increase sales value and local market competitiveness in Meninting Village, West Lombok Regency. The method for implementing the community service program is "training on product innovation and MSME business development to increase sales value and local market competitiveness in Kongok Hamlet, Meninting Village, Batu Layar District, West Lombok Regency" through: 1) Team formation or collaboration between lecturers and KKN students, and the Meninting village government. 2) Training activities in Kongok Hamlet, Meninting Village, involving the community or MSMEs, KKN students, and the village government. The results of the MSME product innovation training activity indicate that the training proceeded smoothly, with stages of material delivery and hands-on practice by participants or the community, particularly in packaging local products or fish pindang. The community appeared to be able to package the products but were hampered by inadequate packaging equipment